Adaptive Depth Imaging With Single-Photon Detectors - Weiji He; Zhenchao Feng; Jie Lin; Shanshan Shen; Qian Chen; Guohua Gu; Beibei Zhou; Ping Zhang (IEEE Photonics Journal)
For active optical imaging, the use of single-photon detectors can greatly improve the detection sensitivity of the system. However, the traditional maximum-likelihood based imaging method needs a long acquisition time to capture clear 3-D image at low light levels. To tackle this problem, we present a novel imaging method for depth estimate, which can obtain the accurate 3-D image in a short acquisition time. Our method combines the photon-count statistics with the temporal correlations of the reflected signal. According to the characteristics of the target surface, including the surface reflectivity, our method is capable of adaptively changing the dwell time in each pixel. The experimental results demonstrate that the proposed method can quickly obtain the accurate depth image despite the existence of strong background noise.